(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper presents recent achievements and original solutions towards increased availability, quality and interoperability of LCID (Life Cycle Inventory Data), developed through European Commission-led activities and based on wide stakeholder consultation and international dialogue. An overview of related activities, such as the ILCD (International Reference Life Cycle Data System), the ELCD (European Reference Life Cycle Database) and the ILCD Entry-Level quality requirements are presented. The focus is then on the LCDN (Life Cycle Data Network).Purpose The European Commission’s Integrated Product Policy Communication, 2003, defined LCA (Life Cycle Assessment) as the ‘best framework for assessing the potential environmental impacts of products’. Since then, the use of LCA and life cycle approaches has been developing in a wide range of European policies, and its use has also significantly grown in business. Increasing the availability of quality-assured LCI (Life Cycle Inventory) data is the current challenge to ensure the development of LCA in various areas. Methods One solution to increase availability is to use LCI data from multiple database sources but under the condition that such LCI data are fully interoperable. A non- centralised data network of LCI datasets complying with minimum quality requirements that was politically launched in 2ND month of 2014, already includes several database nodes from different worldwide sources and has the potential to contribute to the needs of the international community.